Tavshedens terror - Assia Djebar, Derrida og Algeriet - Schmidt, Johanne Gormsen (K&K - Kultur og Klasse, 2015)
Born in Algeria, but educated in the French educational system, Derrida and Djebar both write from a slippery position of in-betweenness, explicitly relating their understanding of language and culture to their problematic, French-Algerian identity. Djebar’s novel, So Vast the Prison, is driven by a desire to hear the beloved, silenced voices of her ancestors, but nevertheless radically opposes the idea of a self-sufficient Algerian identity that has been lost and needs to be salvaged. In Djebar, to track down history is rather like exposing a wound; to realize that the break with the past is unmendable. In keeping with Derrida’s Monolingualism of the Other, the retrospection of So Vast never reaches behind the bilingual condition, suggesting that the colonized is always already entangled in the colonizer. Paradoxically, So Vast presents the colonizer’s silencing of the Algerian people not as the hindrance to, but as the very precondition for liberation, as traces of a Derridean, radically other language resonate from the muffled voices trapped inside the French. Gaining their strength precisely by having no voice and no place, they terrorize the official culture from within, indefatigably destabilizing those phantasms and ideologies that claim to inhabit an unsplit tongue. The Franco-Maghrebian position thus offers a welcome chance of revealing the arbitrariness of the existing law, potentially deconstructing the truth claim of any system.